2006
DOI: 10.1007/s00441-006-0212-6
|View full text |Cite
|
Sign up to set email alerts
|

Larval arm resorption proceeds concomitantly with programmed cell death during metamorphosis of the sea urchin Hemicentrotus pulcherrimus

Abstract: Sea urchins are excellent models to elucidate metamorphic phenomena of echinoderms. However, little attention has been paid to the way that their organ resorption is accomplished by programmed cell death (PCD) and related cellular processes. We have used cytohistochemistry and transmission electron microscopy to study arm resorption in competent larvae of metamorphosing sea urchins, Hemicentrotus pulcherrimus, induced to metamorphose by L-glutamine treatment. The results show that: (1) columnar epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Bar=100 μm feeding behavior which has been shown to be necessary for adult rudiment growth (Yazaki 2002). It is known that sea urchin embryos and larvae can activate physiological mechanisms of programmed cell death at specific developmental stages (Roccheri et al 2002;Sato et al 2006;Vega Thurber and Epel 2007), but an increase of apoptotic processes was observed in response to the accumulation of cadmium in embryos (Agnello et al 2006(Agnello et al , 2007 and larvae (present work). Apoptosis is supposed to be a way of removing cells whose DNA has been heavily damaged by cadmium, as documented in the case of a vertebrate model system (Hamada et al 1997).…”
Section: Discussionmentioning
confidence: 54%
“…Bar=100 μm feeding behavior which has been shown to be necessary for adult rudiment growth (Yazaki 2002). It is known that sea urchin embryos and larvae can activate physiological mechanisms of programmed cell death at specific developmental stages (Roccheri et al 2002;Sato et al 2006;Vega Thurber and Epel 2007), but an increase of apoptotic processes was observed in response to the accumulation of cadmium in embryos (Agnello et al 2006(Agnello et al , 2007 and larvae (present work). Apoptosis is supposed to be a way of removing cells whose DNA has been heavily damaged by cadmium, as documented in the case of a vertebrate model system (Hamada et al 1997).…”
Section: Discussionmentioning
confidence: 54%
“…The major morphological changes that occur during the transition are the resorption of larval tissues, most noticeably the larval arms, and the extrusion and elaboration of the pre-formed juvenile structures, such as the tube feet, which grasp the substrate. In parallel, the larval arms undergo both apoptotic and autophagic cell death [15], and are accompanied by diverse physiological, metabolic and developmental changes (see [16-19] for general description of this process).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, programmed cell death (PCD) process was identified in the sea urchin Hemicentrotus pulcherrimus arms concomitantly with metamorphosis (Sato et al, 2006). It seems possible,…”
Section: Effect Of Dietary Treatments On Larval Growth Morphology Anmentioning
confidence: 99%